Potensi dan Permasalahan dalam Pengembangan Seni Kerajinan Tiohu (Mendong) Gorontalo - I Wayan Sudana; Isnawati Mohamad (LP2M ISBI Bandung, 2023)
Tiohu craft (Fimbristylis globulosa) in Gorontalo has the opportunity to be developed into a creative industry, but in fact the craft just can survive without having significant development. The lack of development on the craft is assumed due to a problem hindering, while its survivability up to now is expected due to the potential that support it. This study aims to analyze the potential and problems in the development of tiohu crafts in Gorontalo. This study employs a qualitative research method with a case study model. Data were collected through observation, interviews, and literature review. Data were analyzed interactively through data reduction, data display, and conclusions. The results showed that the Gorontalo tiohu craft has the potential to be developed but there are problems that hindering. These potentials and problems are revealed from the basic aspects of the craft, namely: the condition of craftspeople, production technology, product form and function, and distribution or marketing. These aspects are interrelated and have a direct influence on the sustainability and direction of its development, therefore it can be used as a basis in formulating strategies on developing Gorontalo tiohu craft in the future or other similar crafts